2020
DOI: 10.1038/s41598-020-61565-3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the effects of smoking on the voice and subjective voice problems using a meta-analysis approach

Abstract: The objectives of this study were to identify the effects of smoking on the voice of smokers and present the baseline data for establishing the basis for preventing voice disorders. This study was evaluated using a meta-analysis from studies published between Jan 1, 2000, and Nov 15, 2018. As a result, the final meta-analysis was conducted using nine papers. The standard mean difference was analyzed after dividing the effects of smoking on voice into the pitch (F0), sound quality (jitter, shimmer, and noise to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 24 publications
2
18
0
Order By: Relevance
“…CS‐induced benign and malignant diseases are not trivial and impair critical laryngeal functions including respiration, coughing, swallowing, and in humans, voice production. Specifically, CS may influence voice production directly by causing inflammation and dehydration of the vocal folds 7 . The larynx is also a target of CS in terms of the significant discomfort associated with smoking 8 .…”
Section: Introductionmentioning
confidence: 99%
“…CS‐induced benign and malignant diseases are not trivial and impair critical laryngeal functions including respiration, coughing, swallowing, and in humans, voice production. Specifically, CS may influence voice production directly by causing inflammation and dehydration of the vocal folds 7 . The larynx is also a target of CS in terms of the significant discomfort associated with smoking 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Second, professionals that require extended periods of voice use, such as teachers, are also exposed to higher risks of vocal hazards 41 . Finally, a recent systematic review on effects of smoking on voice revealed substantial alterations to voice function 42 . In the current investigation, we found that female smokers were particularly sensitive to alterations to their voices as compared to males.…”
Section: Discussionmentioning
confidence: 99%
“… Also, a metanalysis has shown that smoking negatively affects voice pitch, maximum phonation time, voice handicap index, and voice physical subfunctions/domains. …”
Section: Discussionmentioning
confidence: 99%
“…19 Heavy/ extensive smoking may cause irritation and dryness of laryngeal mucosa, which leads to vocal cord inflammation and irritability, which in turn can contribute to cough, respiratory sputum, and voice alterations. 20 Also, a metanalysis has shown that smoking negatively affects voice pitch, maximum phonation time, voice handicap index, and voice physical subfunctions/domains. 20 Increased survival time was also associated with moderate to severe voice and speech scores in the current study.…”
Section: Discussionmentioning
confidence: 99%